The impact of new quality productivity on carbon emission intensity: evidence from China - Xiangke Zhang; Xiangke Zhang; Jia Shen (Frontiers in Earth Science)
The new quality productivity, which integrates the concepts of technological innovation, industrial upgrading, and green development, plays a pivotal role in achieving carbon emission reduction targets. Given that current research on the relationship between new quality productivity and carbon emission intensity remains limited, in order to delve into the impact of new quality productivity on carbon emission intensity, its underlying mechanisms, as well as its heterogeneous performance across different regions and city types, we select panel data from 251 Chinese cities spanning from 2010 to 2021 and conduct an empirical analysis using a panel data two-way fixed-effects model. The research findings reveal that new quality productivity can significantly reduce carbon emission intensity. Further analysis demonstrates that new quality productivity can achieve a reduction in carbon emission intensity by enhancing urban innovation levels and the intensity of government environmental regulations. Moreover, the heterogeneity analysis indicates that, compared with other regions, the inhibitory effect of new quality productivity on carbon emission intensity is more pronounced in the western regions and non-resource-based city samples. This study not only enriches the relevant theories on the relationship between new quality productivity and carbon emissions but also provides a crucial basis for governments to formulate targeted carbon emission reduction policies. Based on this, this paper proposes that investment in areas related to new quality productivity should be increased, technological innovation and industrial upgrading should be promoted, and government environmental regulations should be strengthened. Particular attention should be paid to the development of the western regions and non-resource-based cities to give full play to the role of new quality productivity in carbon emission reduction.